Investigation of temperature and sea level changes in the North Sea for the period 1948-2010 - Chen, Xinping (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2014)
Distribution and changes in sea water temperature and sea level are important items in the hydrographic conditions of the North Sea. The roles played by local air-sea exchange processes and oceanic advection for North Sea temperature variability are investigated in the present study. Furthermore, temperature contributions to sea level changes are evaluated under the influence of the North Atlantic Oscillation (NAO). Analyses are based on model results from the HAMSOM model for the entire North Sea system over the period 1948-2010. For regional ocean models, open boundary conditions (OBCs) are very important and still challenging, especially for long-term simulations. For OBCs, a nudging term added to radiative and/or advective conditions during the wave or slow propagation outward from the model domain of interest is widely used. However, nudging time scales are basically unknown, leading to many empirical selections. In this study, a method for objectively estimating nudging time scales during outward propagation is proposed, by using internal model dynamics near the boundary. We tested this method and other several commonly used OBCs for cases of both an idealized model domain and a realistic configuration, and model results demonstrated that the proposed method improves the model solutions. Many similarities are found between the nudging and mixing time scales, in magnitude, spatial and temporal variations, since the nudging mainly replaces the effect of the mixing terms in this study. However, the mixing time scale is not an intrinsic property of the nudging term because, in other studies, the nudging term might replace terms other than the mixing terms, and thus should reflect other characteristic time scales. From the investigation of the roles of local air-sea exchange processes and oceanic advection in North Sea temperature variability, we found that the seasonal average of surface heat flux (Qsur ) is larger than that of advective heat flux (Qadv ) over much of the North Sea, with an obvious exception ...